1979
DOI: 10.1109/tmag.1979.1060382
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of commercial grade manganese zinc ferrites

Abstract: The microstructures of differently processed Commercial grade MnZn soft ferrites have been studied using transmission electron microscopy and microanalysis, and the microstructural features correlated with the magnetic properties. Special emphasis has been placed on the grain boundaries. The permeabilities range frOm 1200 to 18,000 and loss factors (tan5/p) from 1.0 x 106 to 13.7 x 106 at 50 kHz. The pore distribution in these ferrites was quite diverse although the total porosities are nearly the same. In spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…8 as a function of frequency. Initial permeability of sample B was about 15% smaller than that of sample A compatible with the result of Tsunekawa et al (4), where the lattice parameter increases near the grain boundary and the resonance frequency due to the resonance of domain wall motion and/or spin rotation became higher by due to the incorporation of Ca atoms in the spinel lattice.…”
Section: Resultssupporting
confidence: 88%
“…8 as a function of frequency. Initial permeability of sample B was about 15% smaller than that of sample A compatible with the result of Tsunekawa et al (4), where the lattice parameter increases near the grain boundary and the resonance frequency due to the resonance of domain wall motion and/or spin rotation became higher by due to the incorporation of Ca atoms in the spinel lattice.…”
Section: Resultssupporting
confidence: 88%
“…7,8 Studies of the grain boundary chemistry in combination with grain boundary structural analyses revealed that the grain boundaries are usually a source of stress originating from ZnO evaporation, 9 the presence of a glassy phase on the grain boundary, 10 and segregation of aliovalent ions. 11,12 Microstructural studies of MnZn ferrites showed that not all microstructures composed of grains with overestimated grain size and trapped porosity deteriorate the magnetic permeability of highly permeable MnZn ferrites. Particularly in samples where the pore-to-pore distance is relatively large, the magnetic permeability may lead to a pronounced secondary permeability maximum (SPM) with relatively high permeabilities.…”
Section: Introductionmentioning
confidence: 99%
“…So, it should also be noted that the static dielectric constant of boundary layers are quite different from the bulk grains. In fact, Ca oxides contained in the powder are know to segregate under impurities forms in the boundary regions, producing at these places magnetic and dielectric properties far from that of ferrite crystallites 17,18,19 . Since the ferrite impedance is modelled by series resistance-capacitance elements, the anomalously high apparent dielectric constant of ferrites is a consequence of the high capacitance of the thin boundary regions connected in series by highly conductive bulk grains.…”
Section: Resultsmentioning
confidence: 99%